2020
DOI: 10.1177/0144598720935523
|View full text |Cite
|
Sign up to set email alerts
|

Coal char characteristics variation in the gasification process and its influencing factors

Abstract: Underground coal gasification is a burgeoning coal exploitation technique that coal is directly converted into gaseous fuel by controlled combustion. In this paper, the gasification experiments of Inner Mongolia lignite, Xinjiang subbituminous coal, and Hancheng medium volatile bitumite were conducted respectively by using the tube furnace coal gasification experiment system. The gasification process was conducted under 3°C/min increment within the range of 600–900°C. The gas composition was analyzed by gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…After char characterization result by proximate analysis, it is found that char experiences an increase in Gross Calorific Value grades from 5,804 cal/gr to 6,183 cal/gr and a significant decrease in sulfur levels from 1.18% to 0.38% and also a significant decrease of inherent moisture from 16.10% to 12%. Changes in quality for the better because the coal (lignite type) used is suitable as a raw material, The coal gasification performance with low thermal maturity is obvious better than the high rank coal with higher coalification [29]. The results of the briquette characterization can be seen in Table 9.…”
Section: Resultsmentioning
confidence: 99%
“…After char characterization result by proximate analysis, it is found that char experiences an increase in Gross Calorific Value grades from 5,804 cal/gr to 6,183 cal/gr and a significant decrease in sulfur levels from 1.18% to 0.38% and also a significant decrease of inherent moisture from 16.10% to 12%. Changes in quality for the better because the coal (lignite type) used is suitable as a raw material, The coal gasification performance with low thermal maturity is obvious better than the high rank coal with higher coalification [29]. The results of the briquette characterization can be seen in Table 9.…”
Section: Resultsmentioning
confidence: 99%
“…To explain the difference in the reactivity values of coals, it is also necessary to consider the coal rank. It is known that the coke reactivity increases with the decreasing of coal rank. , Another factor to consider is the alkalinity index (AI) of the ashes. This was calculated from the ash chemical composition using the ratio of the total content of the basic oxides (Fe 2 O 3 , CaO, MgO, Na 2 O, and K 2 O) to the total content of acidic oxides (Al 2 O 3 and SiO 2 ) according to X-ray fluorescence (XRF) analysis (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The pyrolysis solid product coal char of different final pyrolysis temperatures (600°C,750°C, and 900°C) was crushed into 60-80 meshes at and dried for 48 h. The pore variation was measured by ASAP2000; this instrument uses the principle of gas adsorption (typically nitrogen) (Li et al 2020, Yin et al 2020).…”
Section: Samples and Experimentalmentioning
confidence: 99%